Duties And Importance of the Pedagogical Council in Preschool Educational Organizations (Eurasian Scientific Herald, 2023)
The article discusses the organization of pedagogical councils in preschool educational organizations, their structure, tasks performed by pedagogical councils, their importance. , can be used by free and independent researchers.